Subclasses of convex functions on the unit disc of the complex plane - Aron, Mihai (São Paulo Journal of Mathematical Sciences, 2024)
In this paper we introduce some subclasses of normalized univalent functions, more exactly subclasses of S ⋆ , which we will call convex functions of degree n . The main tool used is the idea behind Alexander’s duality theorem between S ⋆ and K . Also, we present a necessary and sufficient condition for convexity of degree n in two complex variables.